The current possible treatment approaches of Polycystic Ovary Syndrome (PCOS) - Justyna Lipińska; Maria Kowalczuk; Łukasz Lipiński; Izabela Kopeć; Jakub Kamiński; Klaudia Klimczak; Laura Loryś; Marcin Narloch; Stanisław Kasprzak; Karolina Kasprzak (Kazimierz Wielki University, 2024)
Introduction             Polycystic ovary syndrome (PCOS), first described by Stein and Leventhal in 1935, is one of the most prevalent endocrine system conditions affecting women of reproductive age. It affects between 6% and 13% of women and the majority of cases are identified between the ages of 20 and 30. Unfortunately, the disease is usually diagnosed only when bothersome symptoms such as hair loss, alopecia, acne, and infertility-related problems occur. Based on the Rotterdam criteria, four phenotypes of PCOS are distinguished. Aim of the study             This review aims to present the current state of knowledge about possible treatment approaches, both non-pharmacological and pharmacological. Materials and methods            The paper was created based on the Pubmed database. The literature was reviewed using the keywords: "PCOS", "PCOS treatment" and " PCOS medications ". The current state of knowledge           Treatments for PCOS must be tailored to the specific needs of each patient. In the management of PCOS, special attention is paid to diet, physical activity, and restoration of the Gut Microbiome. Medications used in therapy are oral contraceptives and anti-androgens, insulin sensitizers, ovulation inducers, calcium and vitamin D supplements, statins, Glucagon-like-peptide-1 (GLP-1) agonists, inositols and interleukin 22 (IL-22)  therapy. Summary            Treatment options for menstrual irregularities and hirsutism are based on the clinical goals and preferences of the patient. The ideal would be causal treatment, but due to the ongoing lack of full understanding of the pathogenesis of the syndrome, is not entirely feasible. The ideal would be causal treatment, but due to the ongoing lack of full understanding of the pathogenesis of the syndrome, is not entirely feasible. The most important is a multimodal approach to treat comorbid conditions such as diabetes mellitus type 2, obesity, hyperlipidemia, depression, and infertility.